Colonization with Enterobacteriaceae producing ESBLs in children attending pre-school childcare facilities in the Lao People's Democratic Republic. (12th February 2015) - Stoesser, Nicole; Xayaheuang, Sivilay; Vongsouvath, Manivanh; Phommasone, Koukeo; Elliott, Ivo; del Ojo Elias, Carlos; Crook, Derrick W.; Newton, Paul N.; Buisson, Yves; Lee, Sue J.; Dance, David A. B.
Abstract: Objectives: Intestinal carriage constitutes an important reservoir of antimicrobial-resistant bacteria, with some of the highest rates reported from Asia. Antibiotic resistance has been little studied in Laos, where some antibiotics are available without restriction, but others such as carbapenems are not available. Patients and methods: We collected stools from 397 healthy children in 12 randomly selected pre-school childcare facilities in and around Vientiane. Colonization with ESBL-producing Enterobacteriaceae (ESBLE) and carbapenemase-producing Enterobacteriaceae (CPE) was detected using a disc diffusion screening test and ESBLE were characterized using WGS. Risk factor data were collected by questionnaire. Results: Ninety-two children (23%) were colonized with ESBLE, mainly Escherichia coli carrying bla CTX-M and Klebsiella pneumoniae carrying bla SHV or bla CTX-M, which were frequently resistant to multiple antibiotic classes. Although residence in Vientiane Capital, foreign travel, higher maternal level of education, antibiotic use in the preceding 3 months and attending a childcare facility with a 'good' level of hygiene were all associated with ESBLE colonization on univariable analysis, a significant association remained only for antibiotic use when a stepwise approach was used with a multivariate random-effects model. WGS analysis suggested transmission in both childcare facilities and community settings. Conclusions: The high prevalence of paediatric colonization with ESBLE in Laos, one of the highest reported in Asia, is probably the result of inappropriate antibiotic use. Paediatric colonization with CPE was not identified in this study, but it is important to continue to monitor the spread of antibiotic-resistant Enterobacteriaceae in Laos.